2021
DOI: 10.22159/ajpcr.2021.v14i5.41116
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition and Toxicity of Stingless Bee Propolis From Various Provinces in Indonesia

Abstract: Objective: The main objectives of the research are to determine the phytochemical content and toxicity of stingless bee propolis from various provinces in Indonesia. Methods: Phytochemical testing of alkaloids and triterpenoids on propolis used a qualitative method, while for testing phenolics, flavonoids, and tannins using quantitative methods. Then, to test the toxicity of stingless bee propolis using the Brine Shrimp Lethality Test method. Results: Propolis with the highest alkaloid and triterpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Studies on the TAC are limited, with some stating the absence of alkaloids as in the case of Indonesian Trigona sp . propolis extracts [ 39 ]. Indian Apis mellifera propolis extract has values ranging from 6.2 to 9.8 mg/100 g which is lower compared to our results [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the TAC are limited, with some stating the absence of alkaloids as in the case of Indonesian Trigona sp . propolis extracts [ 39 ]. Indian Apis mellifera propolis extract has values ranging from 6.2 to 9.8 mg/100 g which is lower compared to our results [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical study of the extract revealed the presence of some metabolites such as polyphenols, flavonoids, saponin, gallic and condensed tannins. However, the presence or not of a certain bioactive compounds in a plant material depends on the specie, the part used and the region where it is found [ 15 , 16 ]. These compounds have lipotropic activities.…”
Section: Discussionmentioning
confidence: 99%
“…This botanical variability contributes to the differences observed in bioactive compound contents not only between the two-propolis types (Pr1 and Pr2) but also in comparison to propolis from various countries, as documented in the literature. 53…”
Section: Bioactive Compoundsmentioning
confidence: 99%